Comparative Genomics of Bacteriophage of the Genus Seuratvirus. (20th December 2017) - Sazinas, Pavelas; Redgwell, Tamsin; Rihtman, Branko; Grigonyte, Aurelija; Michniewski, Slawomir; Scanlan, David J; Hobman, Jon; Millard, Andrew
Abstract: Despite being more abundant and having smaller genomes than their bacterial host, relatively few bacteriophages have had their genomes sequenced. Here, we isolated 14 bacteriophages from cattle slurry and performed de novo genome sequencing, assembly, and annotation. The commonly used marker genes polB and terL showed these bacteriophages to be closely related to members of the genus Seuratvirus . We performed a core-gene analysis using the 14 new and four closely related genomes. A total of 58 core genes were identified, the majority of which has no known function. These genes were used to construct a core-gene phylogeny, the results of which confirmed the new isolates to be part of the genus Seuratvirus and expanded the number of species within this genus to four. All bacteriophages within the genus contained the genes queCDE encoding enzymes involved in queuosine biosynthesis. We suggest these genes are carried as a mechanism to modify DNA in order to protect these bacteriophages against host endonucleases.